2022
DOI: 10.7883/yoken.jjid.2021.355
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Isolation, and Molecular Characterization of <i>Escherichia albertii</i> from Wild Birds in West Japan

Abstract: Escherichia albertii is an emerging zoonotic foodborne pathogen. Several outbreaks of E. albertii have occurred particularly in Japan. Although birds have been considered as one of the most important reservoirs of this bacterium, information regarding the prevalence in birds is still scanty. We performed a survey of E. albertii in wild birds in Japan, and examined characteristics of the isolates. E. albertii specific gene was detected in 5 cloacal swabs out of 156 birds by PCR. Four E. albertii were A c c e p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
(1 reference statement)
2
10
1
Order By: Relevance
“…As discussed above that E. albertii has been identified in various wild mammals and birds [ 3 , 5 , 6 , 15 , 17 , 21 , 22 , 23 , 25 ], however, at present less information is available about characteristics and genomic diversity of E. albertii isolates from wild and safeguarded animals/birds. In the present study, PFGE analysis clearly indicated presence of genetically diverse E. albertii strains among various wild animals even fecal samples collected from them within a limited geographically area ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed above that E. albertii has been identified in various wild mammals and birds [ 3 , 5 , 6 , 15 , 17 , 21 , 22 , 23 , 25 ], however, at present less information is available about characteristics and genomic diversity of E. albertii isolates from wild and safeguarded animals/birds. In the present study, PFGE analysis clearly indicated presence of genetically diverse E. albertii strains among various wild animals even fecal samples collected from them within a limited geographically area ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…E. albertii O-genotypes (EAOgs) of the isolates were examined by PCR assays developed by Ooka et al [ 26 ], which can differentiate 40 O-genotypes (EAOg1 to EAOg40). Pulsed-field gel electrophoresis (PFGE) was performed using Xba I-digested genomic DNA of E. albertii strains isolated from wildlife sources as described previously [ 15 ]. DNA fingerprints obtained were analyzed and phylogenetic tree was constructed by a UPGMA method using a BIONUMERICS software (Fingerprints version 8.0; Applied Maths NV, Sint-Marten-Latem, Belgium).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in 2004, large-scale mortality of a nch species (Carduelis ammea) occurred in Alaska, United States of America (USA), with E. albertii as the probable aetiology (2). Active molecular surveillance studies for E. albertii have since detected the bacterium in dead and apparently healthy birds of multiple orders and species from Australia, Asia and North America (2,(20)(21)(22). Escherichia albertii also has been detected in poultry faeces/GI tract contents and meat (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…raccoon, seal, bat) (8,26,27). Although the occurrence and signi cance to mammal host health remains uncertain, there is a growing body of evidence that avian hosts may act as a reservoir of infection (21,25). Thus, the extent of associated disease in birds and the relationship of bird and human infections requires further investigation.…”
Section: Introductionmentioning
confidence: 99%